Adam Smith on Wages and Education: Some Policy Implications for India. Issue 1 (April 2019) - Thomas, Alex M.
This article outlines Adam Smith's views on wages and education and employs them in providing suggestions for contemporary politics and economic policy. In particular, the joint examination of his concept of 'subsistence wages' and his views on education offer a radically different interpretation of Smith to that found in the mainstream literature. Smith's qualified and nuanced view of wages and education suggests that the market, if left to itself, cannot generate fair wages nor provide inclusive education. Therefore, our contemporary politics and economic policy must incorporate them as central socioeconomic targets.